The Effectiveness of Alternative Dispute Resolution in Trademark Protection in Indonesia: Challenges and Solutions - Ningsih, Novi Rahayu; Karim, Moh. (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2025)
This article examines the challenges and solutions in trademark dispute resolution in Indonesia, with a particular focus on the effectiveness of existing regulations and the implementation of alternative dispute resolution (ADR) methods, such as mediation and arbitration. While Law No. 20 of 2016 provides legal protection for registered trademarks, law enforcement in the digital era faces numerous challenges, including trademark infringements occurring on e-commerce platforms. The article demonstrates that ADR can offer a more efficient and cost-effective alternative to litigation; however, a key challenge lies in the limited awareness among business actors about the benefits of ADR. Consequently, this article recommends enhancing education for business owners, strengthening regulations related to ADR, and improving the quality of mediators and arbitrators in the field of intellectual property law. Furthermore, the article emphasizes the need for integrating technology into the dispute resolution process to improve efficiency and accessibility.